Legal Analysis of the Implementation of Doctor's Authority by Nurses in Emergency Situations Based on Law No 17 Of 2023 (Wanakerta Health Centre and Delima Asih Hospital) - Permana, Diki; RAS, Hernawati; Durahman, Dani (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Delegation of authority in health services in Indonesia is regulated in Article 290 of Law Number 17 Year 2023 on Health, which allows medical personnel (such as doctors) to delegate some of their authority to other health personnel (such as nurses), provided that the recipient has sufficient competence. The purpose of this delegation is to improve the efficiency and effectiveness of services, especially in emergency situations. However, its implementation must be accompanied by accountability, where the doctor as the person in charge of the service (Article 66) can be held legally responsible if malpractice occurs due to supervision or instructions that are not in accordance with standards. This research uses a normative analysis method of the Health Law and its implications in practice. The results show that mediation is the first step in dispute resolution, while compliance with SOPs and good medical documentation are key to preventing legal conflicts. Recommendations include improving the competence of health workers, socialising regulations, strengthening SOPs, and inter-professional collaboration to minimise the risk of malpractice.